2009
DOI: 10.1111/j.1600-9657.2008.00714.x
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of management of dental trauma among medical professionals in Pondicherry, India

Abstract: The aim of the study was to establish the level of knowledge on the management of dental trauma among physicians at Pondicherry, India. A questionnaire was designed and was given to physicians working in medical colleges or as residents in advanced training programs in medicine in Pondicherry, India. The questionnaire contained a clinical situation of tooth avulsion and various treatment options. Only 5.5% of the medical professionals knew about reimplantation and none knew that the patients' mouth was the bes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
86
1
13

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(106 citation statements)
references
References 13 publications
6
86
1
13
Order By: Relevance
“…The findings presented here were consistent with those of other previously published studies. 20,[22][23][24][25] The main reason for the lack of knowledge in this area might be due to the high percentage of participants (87.4%) who stated that they never received any information on what to do if a tooth is knocked out. This is in accordance with the study by Díaz et al 23 They reported 90.2% of nondental professionals in the emergency room had not received any formal training on diagnosis and emergency treatment of dental injuries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings presented here were consistent with those of other previously published studies. 20,[22][23][24][25] The main reason for the lack of knowledge in this area might be due to the high percentage of participants (87.4%) who stated that they never received any information on what to do if a tooth is knocked out. This is in accordance with the study by Díaz et al 23 They reported 90.2% of nondental professionals in the emergency room had not received any formal training on diagnosis and emergency treatment of dental injuries.…”
Section: Discussionmentioning
confidence: 99%
“…In either case, they are frequently first attended by medical professionals in the Emergency Services Department. 22 Many studies were done to evaluate the knowledge of dental professionals and nondental professionals and lay people regarding the management of either TDI in general or specifically in avulsion. 10,12,22 However, only a few studies have been done among medical students.…”
Section: Discussionmentioning
confidence: 99%
“…These surveys have included parents, sport coaches, teachers and even medical doctors. [67891011121314151617181920]…”
Section: Introductionmentioning
confidence: 99%
“…But, few 17.4% of the participants in this study were confident and readily practised placing the tooth back into the socket. Previous studies by Krishnaraj 6 and Holan and Shmueli 7 had reported that only 5.5% and 4% respectively have tried re-implantation.…”
Section: Discussionmentioning
confidence: 99%